STRUCTURAL CAPITAL MEDIATION TO INCREASING THE INFLUENCE OF KNOWLEDGE SHARING ON SUSTAINABLE HIGHER EDUCATION PERFORMANCE - Sutisna, Ade Jaya; Rudiyanto, Rudiyanto (Universitas Bunda Mulia, 2025)
Background: Universities today are navigating increasingly complex challenges, including shifting policy landscapes, technological disruption, and constrained resources. Within this context, knowledge sharing (KS) is recognized as a valuable strategic asset, yet the pathways through which it enhances institutional performance particularly sustainable operational outcomes remain insufficiently articulated.Objective: This research investigates how explicit knowledge sharing (KSE) and tacit knowledge sharing (KST) affect sustainable operational performance (SOP), and whether structural capital (SC) serves as a key intermediary that enables this transformation.Research Methods: A survey-based quantitative design was adopted, targeting both academic and administrative staff in various Indonesian higher education institutions. PLS-SEM was adopted to model the proposed relationships and assess the significance of mediating variables, offering a practical solution for data with complex interdependencies.Research Results: The results demonstrate three core findings. First, both KSE and KST significantly bolster SC, with KST exerting a stronger direct influence. Second, KSE has a notable direct impact on SOP, while the influence of KST on SOP operates predominantly through SC. Third, SC emerges as a critical mediating variable—fully bridging the link between KSE and SOP, and partially mediating the pathway from KST to SOP. These outcomes underscore SC’s central role in converting shared knowledge into operational sustainability.Originality/Novelty of Research: The present study contributes new perspectives to the Knowledge-Based View (KBV) by conceptualizing and validating a model that distinguishes the roles of explicit and tacit knowledge in developing organizational capital. It delivers practical insight for academic leaders by highlighting how strengthening structural capital can enhance the long-term performance of higher education institutions.